A critical study on the legal framework of electronic monitoring of offenders in the prevention of crime in Malaysia / Che Audah Hassan - Hassan, Che Audah (2020)
Electronic monitoring of offenders by way of tagging or devices fitted to the ankle of an offender for the purpose of supervision and monitoring is an advancement in the enforcement of criminal justice system in Malaysia. However, the fitting of an EMD to a body of a person for twenty-hours per day for a certain period ordered by the authority with no possibility of removing may attract an issue of fundamental liberty of the person fitted with the device. Hence, this study will examine the legal framework underlying the provisions of electronic monitoring of offenders in Malaysia under various legislation, the impact that it has on the fundamental liberty of the person tagged with the device, and the effectiveness of the device in the prevention and rehabilitation of offenders. Apart from applying the doctrinal methodology, the researcher has also conducted an interview with many respondents being persons directly involved in the implementation of the law on electronic monitoring. These persons are, police officers, Chairman of Board of Prevention of Crime Act 1959 and Prevention of Terrorism Act 2012, inquiry officers, head of prosecuting officer and the offenders fitted with the device. The main finding of this study supports the crime control model of criminal justice system as the legal framework underlying the objectives of introducing the electronic monitoring of offenders through a device attach to the ankle of the person. Nevertheless, there are some recommendations proposed to improve the implementation of the electronic monitoring devices on offenders such as the data protection laws and the type of device to be attached to the body of the person. Besides, it is suggested that the application of the device is not only used as a tool for monitoring, rather a combination with a program that may encourage in the rehabilitative elements as well as longer resistance of recidivism. Hence, this study will contribute to the literature on electronic monitoring of offenders in the criminal justice and the compliance with the international covenants on the use of the device.